Little critter's this is my friend - Mayer, Mercer, 1943- (New York : Golden Book ; Racine, Wis. : Western Pub. Co., 1989)
Two friends experience the vicissitudes of friendship.
"A Golden easy reader"--Cover.
Keywords: Friendship -- Fiction